A novel technique for seabed strata deformation in situ monitoring - Ge, Yongqiang; Chen, Jiawang; Zhang, Peihao; Cao, Chen; Le, Xiaoling; Ai, Jingkun; Zhou, Peng; Liang, Tao (Frontiers in Marine Science, 2022)
Seafloor strata deformation monitoring is important for gas hydrate exploitation and the monitoring and early warning of seabed instabilities. Due to the limitation of in-situ monitoring technology, existing observations are carried out with geophysical methods to provide basic geomorphological characteristics and stratigraphic structures. However, it is of equal importance to study the in-situ evolution mechanism of the process of strata deformation, which relies heavily on long-term in-situ observations. A field monitoring instrument for seabed strata deformation monitoring is presented. Sufficient theoretical, numerical and experimental were carried out to mechanical analysis on the entire deployment process of the monitoring instrument. The maximum penetration resistance and reaming pressure were calculated during deployment process, the stability and feasibility of the deployment method were verified. To validate the maximum penetration resistance obtained, and the monitoring ability of the instrument, field tests were conducted on a tidal flat in Changzhi island. The penetration resistance and the strata deformation of the tidal flat are measured. The results demonstrate the feasibility of the presented instrument for seabed strata deformation monitoring.